An Improvement Of Shunt Active Power Filter Using Effective Controller For Different Load Condition - Omar, Rosli; Tan, Zi Hao; Jubair Al-Hiealy, Mohammed Rasheed; Sulaiman, Marizan (Medwell Publications, 2020)
The distorted waveforms due to highly uses of the non-linear load, especially, the current that is considered the main issues need to be addressed seriously. The issues of the distorted waveforms for the current have attracted many researchers to recover them in the electrical system. There are so, many electronic devices that have been used in order to protect the waveform of the current from distorted as it is very dangerous and may cause the main supply to shut down or burnt. The main aims of this project is to design and develop a shunt active power filter for the purposes to mitigate the distorted of current waveform produced by the different types of non-linear loads using the controller of the SRF. The software MATLAB/Simulink will be used to design and develop shunt active power filter and its controller. Finally, the performance of the shunt active power filter and its controller at different types of non-linear loads will be evaluated through the waveforms of the currents produced by different types of non-linear loads and the Total Harmonic Distortion (THD) will be monitored and observed whether meets to the International Electrical Committee (IEC) standard or not.